Helping and healing : religious commitment in health care - Pellegrino, Edmund D., 1920-2013 (Georgetown University Press, 1997)
Helping and Healing looks at the ways a religious perspective shapes the healing relationship and the ethics of that relationship. Pellegrino and Thomasma seek to clarify the role of religious belief in health care by providing a moral basis for such commitment as well as a balancing role for reason. This book establishes a common ground for believers and skeptics alike in their dedication to relieve suffering by showing that helping and healing require an involvement in the religious values of patients. It clearly argues that religion provides crucial insights into medical practice and morality that cannot be ignored, even in our morally heterogeneous society. Physicians, nurses, administrators, clergy, theologians, and other health professionals and church leaders will find that this volume will help them reflect on the role of religion in the health care ministry and make a religious commitment integral to their professional lives.